The Factors for Purchasing Skincare Products - Sernanda, Bella Cahyu; Prihandono, Dorojatun (Universitas Negeri Semarang, 2021)
The beauty industry in Indonesia is growing quite rapidly. This has resulted in increasingly fierce competition in the cosmetics and skincare business. This study aims to examine the effect of celebrity endorser, sponsorship, and product quality on purchasing decisions through buying interest in consumers of the Asa Beauty MS Glow store in Semarang. The populations in this study are customers or users of MS Glow. The sampling technique used is non-probability sampling with purposive sampling technique, obtained 100 samples, namely MS Glow users as respondents in this study. The data analyzed by quantitative method using path analysis through the IBM SPSS 24 software. The results showed that the celebrity endorser, sponsorship, and product quality variables have a positive and significant effect on purchasing decisions. Path analysis test results showed that buying interest is able to mediate celebrity endorser, sponsorship, and product quality, and also it has a positive and significant influence on purchasing decisions.